Effects of mixing state of composite powders on sintering behavior of cathode for solid oxide fuel cells - Park, Mansoo; Jung, Hwa Young; Kim, Jeong Yun; Kim, Hyoungchul; Yoon, Kyung Joong; Son, Ji-Won; Lee, Jong-Ho; Kim, Byung-Kook; Lee, Hae-Weon (ELSEVIER SCI LTD, 2017)
For efficient development of high-performance composite electrodes for solid oxide fuel cells (SOFCs), it is crucial to precisely tailor the microstructural features of the electrodes, such as their grain size, phase connectivity, and pore structure. Herein, we report the effects of the mixing state of component powders of a composite cathode composed of Sr-doped LaMnO3 (LSM) and yttria-stabilized zirconia (YSZ) on its sintering behavior. LSM-YSZ composite powders were synthesized by a particle-dispersed glycine-nitrate process using YSZ particles as inclusions in the LSM precursor solution. The dispersion state of the YSZ particles in the solution was varied from a well-dispersed state to a highly flocculated state through adjustment of the amount of adsorbed polyethylene glycol. The dispersion state of the component powders was found to strongly impact the densification behavior of the composite, which was explained by the formation of a continuous network of the "slow-sintering" inclusion particles. A highly porous structure with phase connectivity and sufficient triple phase boundaries could be achieved by enhancing the mixing homogeneity and optimizing the mixing scale. The proposed concept provides new insights into the microstructural evolution of composites in constrained sintering, and it could potentially enable development of the ideal electrode structure for SOFCs.
Keywords: TEMPERATURE SOFC APPLICATIONS; ELECTROCHEMICAL PERFORMANCE; IMPEDANCE SPECTROSCOPY; 3-DIMENSIONAL MICROSTRUCTURE; DENSIFICATION; INCLUSIONS; OPTIMIZATION; ELECTROLYTE; COMPACTS; MATRIX